2020
DOI: 10.3390/s20082399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Elastomer Matrix on Thermoplastic Elastomer-Based Strain Sensor Fiber Composites

Abstract: In this study, a thermoplastic elastomer sensor fiber was embedded in an elastomer matrix. The effect of the matrix material on the sensor properties and the piezoresistive behavior of the single fiber-matrix composite system was investigated. For all composites, cycling test (dynamic test) and the relaxation behavior at different strains (quasi-static test) were investigated. In all cases, dynamic properties and quasi-static significantly changed after embedding, compared to the pure fiber. The composite with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…The ShA70 sensor fiber composites exhibit a slightly higher sensitivity, expressed by a larger gauge factor. This observation is in good agreement with a previous work by Georgopoulou et al Therein, it was reported that for stiffer matrix materials, higher sensitivity can be achieved [ 41 ]. It can be seen in Table 1 from the values of the initial resistance that for composites made with the two different fibers, with increasing the shore hardness of the matrix, the conductivity increased.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The ShA70 sensor fiber composites exhibit a slightly higher sensitivity, expressed by a larger gauge factor. This observation is in good agreement with a previous work by Georgopoulou et al Therein, it was reported that for stiffer matrix materials, higher sensitivity can be achieved [ 41 ]. It can be seen in Table 1 from the values of the initial resistance that for composites made with the two different fibers, with increasing the shore hardness of the matrix, the conductivity increased.…”
Section: Resultssupporting
confidence: 93%
“…For that reason, elastomer materials like silicone rubber are excellent candidates for the development of sensorized robotic skin. To avoid stiffening of the resulting composite, Georgopoulou et al have demonstrated that using the fiber composite concept, a higher stiffness of flexible elastomer strain sensor composites can be avoided [ 41 , 42 ]. Typically, these sensorized robotic skins are mainly produced by hand-made casting process.…”
Section: Introductionmentioning
confidence: 99%
“…For ShSF fabrication a capillary rheometer Rh7 (Netzsch Gerätebau GmbH, Selb, Germany) was used. This process for the fabrication of piezoresistive fiber sensors based on thermoplastic elastomers has been described elsewhere [ 7 , 44 ]. The extrusion was performed at a temperature of 95 °C with a 0.5 mm die.…”
Section: Methodsmentioning
confidence: 99%
“…7 When there are continuous cycles of straining and releasing, the sensitivity can change and the GF should be calculated in the new cycles, to show how the sensitivity is affected by the signal drift. 31 The GF as an indicator of the sensitivity of a piezoresistive sensor provides no information about the range of the strains the sensor can be used. It has been suggested that the product of the gauge factor and the strain range should be used instead of the gauge factor as a measure of the good performance of a sensor.…”
Section: Characterization Of the Piezoresistive Response 21 Sensitivitymentioning
confidence: 99%
“…82 It has been reported that the sensors with silver nanowires based on silicone elastomers have very high sensitivity (GF=926 at ε=10%) but the function of the sensor at higher strains than 50% was not reported. 31 In another attempt, silver nanowires and silver nanoparticles were combined to produce a silicon elastomer composite sensor, and the results showed a very high gauge factor of 3766 with good linearity in a range of strains 0-28%. Unfortunately, this sensor was not investigated at higher strains.…”
Section: Silicone Elastomersmentioning
confidence: 99%